Roadmap of reforming the system of sociomedical assessment Ukraine’s - Mykychak , I.V.; Perepelychna, R.Ya.; Borysova , I.S. (Medicni Perspektivi, 2022)
Roadmap of reforming the system of sociomedical assessment Ukraine’s